1980
DOI: 10.2172/6214193
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion near buildings as determined from atmospheric tracer experiments. Technical report

Abstract: Data from the innsrmost arcs and roof top samplers of the Rancho Seco and EOCR field studie; were used to examine diffusion close to a building. The minimum length plume paths were determined from each release location to each sampler position at these two test sites. Measured concentrations, normalized by source strength (C/Q), were plotted versus plume path length and an envelope containing 95% of the measured values of C/Q was determined. The curves from the two sites were similar in shape and implied three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Over the years, many tracer field studies have been conducted investigating dispersion in individual street canyons (e.g., Huang et al 2000;DePaul and Sheih 1985), around individual buildings (e.g., Oikawa and Meng 1997;Jones and Griffiths 1984;Ogawa and Oikawa 1982), through multibuilding and industrial complexes (e.g., Thistle et al 1995;Guenther et al 1990;Sagendorf et al 1980), and through urban areas (e.g., Cooke et al 2000;McElroy 1997;Allwine et al 1992;Gryning and Lyck 1984). Additionally, numerous wind tunnel and laboratory studies have been conducted investigating flows and diffusion around idealized structures, individual buildings, and industrial complexes (e.g., Zhang et al 1996;Higson et al 1994;Mirzai et al 1994;Ramsdell 1990;Huber 1989;Hosker 1987;Hosker 1984;Huber and Snyder 1982;Allwine et al 1980;Abbey 1976).…”
mentioning
confidence: 99%
“…Over the years, many tracer field studies have been conducted investigating dispersion in individual street canyons (e.g., Huang et al 2000;DePaul and Sheih 1985), around individual buildings (e.g., Oikawa and Meng 1997;Jones and Griffiths 1984;Ogawa and Oikawa 1982), through multibuilding and industrial complexes (e.g., Thistle et al 1995;Guenther et al 1990;Sagendorf et al 1980), and through urban areas (e.g., Cooke et al 2000;McElroy 1997;Allwine et al 1992;Gryning and Lyck 1984). Additionally, numerous wind tunnel and laboratory studies have been conducted investigating flows and diffusion around idealized structures, individual buildings, and industrial complexes (e.g., Zhang et al 1996;Higson et al 1994;Mirzai et al 1994;Ramsdell 1990;Huber 1989;Hosker 1987;Hosker 1984;Huber and Snyder 1982;Allwine et al 1980;Abbey 1976).…”
mentioning
confidence: 99%
“…Sagendorf et al 7 conducted a series of tests involving the release of a tracer gas and measurement of its concentration near two large nuclear facilities. The results from these tests were in good agreement with the predictions of Wilson's model, and showed that the appropriate wind speed, U, for calculating dilution is the undisturbed flow speed upwind of the building.…”
Section: Models Of the Form: D Mln = B X ^ ( £-Vmentioning
confidence: 99%
“…46 More recent studies include Huntington Canyon, 67 Clinch River, 68 low wind inversion conditions, 69 Garfield smelter, 70 Rancho Seca, 71 and additional studies in the vicinity of a reactor building. 72 Many urban studies also contributed to the knowledge of meteorological influences on pollutants. An early comprehensive study conducted mostly before World War II in Leicester, England was reported by the Department of Scientific and Industrial Research.…”
Section: Measured Concentrationsmentioning
confidence: 99%